2009
DOI: 10.1128/aac.01022-08
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and Bactericidal Activities of Daptomycin, Vancomycin, and Teicoplanin against Methicillin-Resistant Staphylococcus aureus Isolates Collected from 1985 to 2007

Abstract: The inhibitory and bactericidal activities of daptomycin, vancomycin, and teicoplanin against a collection of 479 methicillin-resistant Staphylococcus aureus isolates were assessed. The isolates were collected from U.S. and European hospitals from 1985 to 2007 and were primarily from blood and abscess cultures. The MICs and minimum bactericidal concentrations (MBCs) of the three agents were determined, and the MBC/MIC ratios were calculated to determine the presence or absence of tolerance. Tolerance was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 25 publications
0
34
1
2
Order By: Relevance
“…All S. aureus isolates tested so far demonstrate an MBC/MIC ratio of 1 or 2, indicating rapid bactericidal activity of DAP (43)(44)(45). The DAP MBC/MIC ratios varied among the four VGS strains in this study (from 4 to 16) and were higher than the values seen with S. aureus.…”
Section: Discussioncontrasting
confidence: 41%
“…All S. aureus isolates tested so far demonstrate an MBC/MIC ratio of 1 or 2, indicating rapid bactericidal activity of DAP (43)(44)(45). The DAP MBC/MIC ratios varied among the four VGS strains in this study (from 4 to 16) and were higher than the values seen with S. aureus.…”
Section: Discussioncontrasting
confidence: 41%
“…If the compromise of bactericidal activity by tolerance has clinical implications, then the magnitude of the tolerance problem should be measured. Whilst some studies set at 15% vancomycin tolerance in wild-type MRSA [8], a recent study reported rates of 18%, 6.1% and 0% to teicoplanin, vancomycin and daptomycin, respectively [9].…”
Section: Discussionmentioning
confidence: 98%
“…The most frequent resistance phenotype is the heterogeneous vancomycin-intermediate-resistant S. aureus (hVISA), ranging from 0% to 50% in different studies, followed by homoresistant vancomycin-intermediate S. aureus (VISA) (10% of all vancomycin-intermediate-resistant isolates) and with inappreciable spread of vancomycin-resistant S. aureus (VRSA) strains [2][3][4][5][6][7]. Vancomycin tolerance is defined as a minimum bactericidal concentration:minimum inhibitory concentration (MBC:MIC) ratio of ≥32 or an MBC:MIC ratio ≥16 with an MBC value in the resistant range [8,9] and it can be assumed that 100% of VISA and VRSA, 74% of hVISA and 15% of wild-type MRSA are tolerant to this antibiotic 0924-8579/$ -see front matter © 2009 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…(24) yaptıkları çalışmada daptomisin, vankomisin ve teikoplanin için MİK ve minimum bakterisidal konsantrasyon oranlarını kıyaslamışlar ve en etkin antibiyotiğin daptomisin olduğu sonucuna varmışlardır.…”
Section: Discussionunclassified